Prevalence of spontaneous type I ECG pattern, syncope, and other risk markers in sudden cardiac arrest survivors with Brugada syndrome - Leong,KMW; Ng,FS; Jones,S; Chow,J-J; Qureshi,N; Koa-Wing,M; Linton,NWF; Whinnett,ZI; Lefroy,DC; Davies,DW; Lim,PB; Peters,NS; et al. (PACE - Pacing and Clinical Electrophysiology, 2019)
IntroductionA spontaneous type I electrocardiogram (ECG) pattern and/or unheralded syncope are conventionally used as risk markers for primary prevention of sudden cardiac arrest/death (SCA/SCD) in Brugada syndrome (BrS). In this study, we determine the prevalence of conventional and newer markers of risk in those with and without previous aborted SCA events.MethodsAll patients with BrS were identified at our institute. History of symptoms was obtained from medical tests or from interviews. Other markers of risk were also obtained, such as presence of (1) spontaneous type I pattern, (2) fractionated QRS (fQRS), (3) early repolarization (ER) pattern, (4) late potentials on signalaveraged ECG (SAECG), and (5) response to programmed electrical stimulation.ResultsIn 133 patients with Bars, 10 (7%) patients (mean age = 39 ± 11 years; nine males) were identified with a previous ventricular fibrillation/ventricular tachycardia episode (n = 8) or requiring cardiopulmonary resuscitation (n = 2). None of these patients had a prior history of syncope before their SCA event. Only two (20%) patients reported a history of palpitations or dizziness. None had apneic breathing and three (30%) patients had a family history of SCA. From their ECGs, a spontaneous pattern was only found in one (10%) of these patients. Further, 10% of patients had fQRS, 17% had late potentials on SAECG, 20% had deep S waves in lead I, and 10% had an ER pattern in the peripheral leads. No significant differences were observed in the nonSCA group.ConclusionThe majority of BrS patients with previous aborted SCA events did not have a spontaneous type I and/or prior history of syncope. Conventional and newer markers of risk appear to only have limited ability to predict SCA.